Enlarged exact compensation in distributed systems - Afifi, Larbi; Chafiai, Abdelhakim; Bel Fekih, Abdelaziz (Zielona Góra: Uniwersytet Zielonogórski)
In this work, we examine, through the observation of a class of linear distributed systems, the possibility of reducing the effect of disturbances (pollution, etc.), by making observations within a given margin of tolerance using a control term. This problem is called enlarged exact remediability.
Keywords: distributed systems; remediability; control; actuators; sensors